2013
DOI: 10.1007/s40003-012-0043-5
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic Variation in Root Anatomy, Starch Accumulation, and Protein Induction in Upland Rice (Oryza sativa) Varieties Under Water Stress

Abstract: Rice (Oryza sativa L.) roots play important role in the absorption of water, nutrients, and also in stress tolerance such as desiccation, salt and drought stress. The root's anatomical and histological features showed large xylem vessels and reduced aerenchyma formation in resistant genotypes under water stress. Correlation of anatomical changes in parenchymatous cortex region, starch accumulation in the cortex, and outer unicellular layer of epiblema was also found in rice var. Nagina 22, the most acclaimed d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 39 publications
3
11
0
Order By: Relevance
“…A recent study showed that root cortex thickness was reduced in sensitive varieties of rice subjected to water deficit [28]. Cortical parenchyma might serve as a storage area of nutrients and water [29]. In our study, the decrease in root parenchymatic cell size, suggest an important role in determining reactions to drought in A. gombiformis roots.…”
Section: Discussionsupporting
confidence: 62%
“…A recent study showed that root cortex thickness was reduced in sensitive varieties of rice subjected to water deficit [28]. Cortical parenchyma might serve as a storage area of nutrients and water [29]. In our study, the decrease in root parenchymatic cell size, suggest an important role in determining reactions to drought in A. gombiformis roots.…”
Section: Discussionsupporting
confidence: 62%
“…Large xylem conduits with a low resistance to water flow and high theoretical hydraulic capacity might compensate for lower water uptake from shallower and lesser-branched root systems. A similar pattern was noted by Singh et al [32] on the rice root's anatomical and histological shifts towards larger xylem vessels under water stress in resistant genotypes. The same strategy was concluded by Von Arx et al [13], where upon release from drought stress, long-living perennial herb plants of Potentilla diversifolia were able to shift the vessel sizes towards larger diameters, enabling them to utilize increased soil moisture.…”
Section: Discussionsupporting
confidence: 87%
“…Root represents the first plant organ that detects a limitation of the water supply in the soil and a defective root system due to damages from drought stress impairs plant survival 27 . Cortical parenchyma serves as a storage area of nutrients and water 28 . Air spaces in cortical tissue due to collapsed cells could interrupt radial water movement in roots and reduce root/soil contact because of root shrinkage away from the soil thus limiting water uptake in drying soils 29 .…”
Section: Discussionmentioning
confidence: 99%